Trends in VET policy in Europe 2010-12 : progress towards the Bruges communiqué - (:unkn) unknown (Publications Office of the European Union, 2012)
This report analyses progress towards towards the 22 short-term deliverables defined in the Bruges communiqué of 2010. "Attention has clearly focused on helping young people remain in, and return to, education and training through work-based learning routes. Building on their joint work in the last decade, countries have advanced in setting up qualifications frameworks and devising approaches to assure quality in VET, but much work is still in the planning stage. More attention to the professional development of VET staff, better monitoring of VET labour market outcomes, and considering incentives where appropriate, could help progress in the coming years." (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2 Europa; EU-Bildungspolitik; Berufsbildung; Indikatoren; Monitoring; Europa